2015
DOI: 10.1002/pro.2688
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific yet decisive: Ubiquitination can affect the native‐state dynamics of the modified protein

Abstract: Ubiquitination is one of the most common post-translational modifications of proteins, and mediates regulated protein degradation among other cellular processes. A fundamental question regarding the mechanism of protein ubiquitination is whether and how ubiquitin affects the biophysical nature of the modified protein. For some systems, it was shown that the position of ubiquitin within the attachment site is quite flexible and ubiquitin does not specifically interact with its substrate. Nevertheless, it was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 85 publications
(111 reference statements)
2
18
0
1
Order By: Relevance
“…2 and SI, Figure S6). This discussion is consistent with a recent computational study, which showed that a ubiquitylation-induced increase in entropy in the folded state of the substrate protein causes thermodynamic destabilization20. Furthermore, the induction of more anisotropic molecular motion by ubiquitylation may be a possible factor that causes these changes in the structural dynamics of the substrate proteins.…”
Section: Discussionsupporting
confidence: 91%
“…2 and SI, Figure S6). This discussion is consistent with a recent computational study, which showed that a ubiquitylation-induced increase in entropy in the folded state of the substrate protein causes thermodynamic destabilization20. Furthermore, the induction of more anisotropic molecular motion by ubiquitylation may be a possible factor that causes these changes in the structural dynamics of the substrate proteins.…”
Section: Discussionsupporting
confidence: 91%
“…Hagai and Levy note that the thermodynamic effects of ubiquitination vary depending on the attachment site [ 118 ]. Atomistic MD simulations also show that ubiquitination of Ubc7, an E2 enzyme, decreases the flexibility of certain regions of Ubc7 although there were no specific direct interactions between ubiquitin and the E2 [ 120 ]. We observe similar stabilization of the C-helix with ubiquitination at K476, also in the absence of any stable interactions between ubiquitin and ZAP-70.…”
Section: Discussionmentioning
confidence: 99%
“…We observe similar stabilization of the C-helix with ubiquitination at K476, also in the absence of any stable interactions between ubiquitin and ZAP-70. The Ubc7 simulations also show that the strongest effect occurred with K48-linked tetraubiquitination at known sites of degradative ubiquitination [ 120 ], indicating that polyubiquitination could have an even larger effect on ZAP-70 conformation than monoubiquitination.…”
Section: Discussionmentioning
confidence: 99%
“…A couple of arguments assert that ubiquitin conjugates must be removed during triage: 1. Ubiquitin conjugation influences protein folding dynamics, thwarting the possibility of appropriate refolding [55]. 2.…”
Section: Deubiquitylation Activity Is Required For Transient-qc Clearmentioning
confidence: 99%